COMPARISON OF STUDENT ATTITUDES TOWARD NATURAL SCIENCES IN RURAL MIDDLE SCHOOLS IN JAMBI PROVINCE - Tanti Tanti; Dwi Agus Kurniawan; Rahmat Perdana; Orin Hidayusa Wiza (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2020)
The purpose of this study is to determine the assessment of students’ attitude of science subjects in several indicators. This type of research is quantitative research with inferential statistical data. This study involved two different schools, namely SMP 17 Batanghari Regency with a sample obtained by 140 students and SMP 3 Muaro Jambi with a sample of 145 students. The students’ attitudes were noticed in several indicators, namely the social implications of science, the adoption of science attitudes and the enjoyment of learning science. As the result, from the three indicators, the attitude of the SMP 3 Muaro Jambi students were dominantly in good category, whereas those of the students in Batanghari District were dominantly in quite good category. In conclusion, there were differences between the two school students’ attitude toward natural science which was reinforced by the results of t tests that have been done.